2018
DOI: 10.1021/acs.jpcb.8b03390
|View full text |Cite
|
Sign up to set email alerts
|

Probing Phase Evolutions of Au-Methyl-Propyl-Thiolate Self-Assembled Monolayers on Au(111) at the Molecular Level

Abstract: A self-assembled monolayer (SAM) consisting of a mixture of CHS-Au-SCH, CHS-Au-S(CH)CH, and CH(CH)S-Au-S(CH)CH was studied systematically using scanning tunneling microscopy and density functional calculations. We find that the SAM is subjected to frequent changes at the molecular level on the time scale of ∼minutes. The presence of CHS or CHS-Au as a dissociation product of CHS-Au-SCH plays a key role in the dynamical behavior of the mixed SAM. Slow phase separation takes place at room temperature over hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…It may be of interest to examine this transition in greater detail, as it may be that the transition to the 2D gas phase occurs when the Au­(CH 3 S) 2 molecules themselves begin to break up. There is clear evidence that the RS–Au–SR staple breaks into RS and Au–SR at RT from surface reactions involving thiols of different alkane chain lengths. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be of interest to examine this transition in greater detail, as it may be that the transition to the 2D gas phase occurs when the Au­(CH 3 S) 2 molecules themselves begin to break up. There is clear evidence that the RS–Au–SR staple breaks into RS and Au–SR at RT from surface reactions involving thiols of different alkane chain lengths. , …”
Section: Resultsmentioning
confidence: 99%
“…There is clear evidence that the RS−Au−SR staple breaks into RS and Au−SR at RT from surface reactions involving thiols of different alkane chain lengths. 14,15 4. CONCLUSIONS In summary, a number of interesting dynamical processes have been studied in the low-coverage row phase of CH 3 S−Au− SCH 3 on Au(111).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that "conflicted" SAM-based interfaces generated from bidentate spiroalkanedithiols possessing mixed hydrocarbon and fluorocarbon tailgroups exhibit enhanced protein resistance when compared to SAMs generated from their single-component monodentate counterparts [41]. Moreover, the generation of SAMs from dithiol-based adsorbates permits studies of the behavior and properties of interfaces consisting of homogeneously mixed disparate chemical species [38][39][40][41] that would typically phase-separate to form surfaces having patches of single-component domains [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The strong Au-S chemical affinity has been used to design different molecule-metal systems from the adsorption of organosulphur compounds on gold surfaces, specially the Au(111) surface. [5][6][7] In particular, when this kind of compounds present π delocalized electrons, they exhibit various interesting functionalities (e.g. photochromism, magnetism, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of organosulfur compounds on gold surfaces have drawn a great interest in fields such as single-molecule junctions, self-assembly and electronic devices. The strong Au–S chemical affinity has been used to design different molecule–metal systems from the adsorption of organosulfur compounds on gold surfaces, specially the Au(111) surface. In particular, when these compounds present π-delocalized electrons, they exhibit various interesting functionalities (e.g., photochromism, magnetism, etc. ), which make them ideal active components to build up nanodevices. However, despite the strength of Au–S bond, the geometry of molecules adsorbed on metal surfaces also depends on non-covalent interactions like the host–guest interactions, electrostatic interactions and metal–ligand interactions. , The latter are closely related to the functionality of the molecular headgroup.…”
Section: Introductionmentioning
confidence: 99%